Дія дисциплінарних преюдицій у кримінальному процесі - Шилін, Денис Вікторович; Шилин, Денис Викторович; Shilin, Denis (Одеса : Юрид. л-ра, 2012)
The article is dedicated to the complex analysis of applying prejudices in criminal procedure, detection of the possible ways of improvement of the mechanism of realization disciplinary prejudices in criminal procedure. The author deals the mechanism of realization disciplinary prejudices in criminal process.
Шилін Д. В. Дія дисциплінарних преюдицій у кримінальному процесі / Д. В. Шилін // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 564-570.
Keywords: дисциплінарна преюдиція; преюдиціальність; доказування у кримінальному процесі; дисциплинарная преюдиция; преюдициальность; доказывание в уголовном процессе; disciplinary prejudice; prejuciality; proving in criminal process